Fungsi Upacara Adat Kenduri Pusako dalam Kehidupan Sosial Masyarakat Kecamatan Kumun Debai Sungai Penuh - Roby Masfian Dori; Febri Yulika; Edi Satria (Ethnography : Journal of Cultural Anthropology, 2021)
The study, titled “the Function of Ceremonial Feast Pusako In the Social Life of the People of the District Kumun Debai, Kota Sungai penuh, Jambi Province”, aimed to describe about the Process and Functionality of a traditional ceremony Kenduri Pusako. This research is a Qualitative research, the theory used in this research is the theory of Functionalism, the method used is qualitative research method with data collection techniques through interviews, literature study, observation, and documentation.Ceremonial Feast Pusako is the traditional ceremony of the largest in the District Kumun Debai, in the ceremonial Feast Pusako there are two the main event, namely, the Coronation of the Title and the Decline of the Heirlooms. From the results of research conducted, there are some functions that are contained in the ceremonial Feast Pusako, including Social Functions, the Function of Carrying Sko, Function Reading a Brief History of Depati IV District Kumun Debai, the Function of the Inauguration of Depati Ninik Mamak, Function Heirlooms, the Function of Art, the Function of Cultural Preservation, Economic Function, the Function of Ritual and the Function of Education.